2014
DOI: 10.1038/srep05018
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Arabidopsis MYB transcription factor, AtMYB111, in tobacco requires light to modulate flavonol content

Abstract: Flavonoids, due to their pharmacological attributes, have recently become target molecules for metabolic engineering in commonly consumed food crops. Strategies including expression of single genes and gene pyramiding have provided only limited success, due principally to the highly branched and complex biosynthetic pathway of the flavonoids. Transcription factors have been demonstrated as an efficient tool for metabolic engineering of this pathway, but often exhibit variation in heterologous systems relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 46 publications
3
64
0
2
Order By: Relevance
“…The overexpression of the TFs belonging to the classical ABA-dependent or ABA-independent pathways, such as nitrogene assimilation control (NAC), basic leucine zipper (Bzip), myeloblastosis oncogene (MYB), myelocytomatosis oncogene (MYC), and dehydration-responsive element binding (DREB), promotes tolerance to drought stress in different species, including Arabidopsis, rice, and soybean (Le et al 2011;Xu et al 2011;Pandey et al 2014;Miyamoto et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of the TFs belonging to the classical ABA-dependent or ABA-independent pathways, such as nitrogene assimilation control (NAC), basic leucine zipper (Bzip), myeloblastosis oncogene (MYB), myelocytomatosis oncogene (MYC), and dehydration-responsive element binding (DREB), promotes tolerance to drought stress in different species, including Arabidopsis, rice, and soybean (Le et al 2011;Xu et al 2011;Pandey et al 2014;Miyamoto et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The flavonol-specific MYBs induced the expression of structural genes such as CHS, CHI, F3H, and FLS1 of the phenylpropanoid pathway (Stracke et al, 2007;Dubos et al, 2010;Xu et al, 2015). Previously, a plethora of reports suggested that the expression of such MYBs in tobacco (Nicotiana tabacum) and tomato enhances the expression of structural genes of the pathway leading to enhanced flavonoid content, nutritional quality, and insect resistance (Luo et al, 2008;Misra et al, 2010;Pandey et al, 2012Pandey et al, , 2014aPandey et al, , 2014bPandey et al, , 2015aPandey et al, , 2015bChoudhary et al, 2016). Here, we describe the participation of miR858a in the transcription factor regulon responsible for the biosynthesis of flavonoids and development in Arabidopsis.…”
Section: Mir858a-mediated Regulation Affects the Phenylpropanoid Pathwaymentioning
confidence: 99%
“…Flavonoids such as flavonols, flavones, isoflavones, and flavan-3-ols were identified in Cornaceae, Fabaceae, and Rosaceae. Flavonoids, the phenolic compound of plants, have been studied for their chemical diversity and associated roles including bioactivities, insect resistance, and defense metabolites (Pandey et al 2014). Flavonoid metabolism leading to the biosynthesis of lignins and sinapate esters consists of numerous intermediates including isoflavones, flavones, flavonols, flavandiols, chalcones, and anthocyanins (Winkel-Shirley 2001).…”
Section: Metabolic Pathway Correlations and The Relative Contents Of mentioning
confidence: 99%